BLENDED LEARNING AS A MEANS OF FUTURE PRIMARY SCHOOL TEACHER PROFESSIONAL DEVELOPMENT - Oliiar, Mariia; Fomin, Kateryna (Mountain School of Ukrainian Carpaty, 2022)
The research aims to prove that the modern education system is designed to respond to the civilizational and sociotechnological challenges of the 21st century. The new content of education is based on the formation of competencies necessary for the individual’s successful self-realization in society. The COVID‑19 pandemic and the war in Ukraine have become additional stimulus for the creation of new educational products, in particular for the development of the digitalization of education, and blended learning practices. In scientific studies of domestic and foreign scientists, the necessity to implement flexible innovative models of higher education, the priority of using digital teaching tools, and the growing demand for the training of modern specialists in a digital environment can be found. Accordingly, new, more complex requirements apply to future teachers' professional training, in particular primary school teachers. Objectively, the necessity to understand modern digital didactics, develop measures to support students and teachers, and new models of education are in great demand. One of the tools of such a transformation is blended learning, which has been actively developing in recent decades and ensures the orientation of the educational process to the formation of a new model of a graduate taking into account modern standards. The article, based on the study of the pedagogical possibilities of blended learning technology, analyzes the advantages and disadvantages of this technology in the process of future primary school teachers’ professional training. The authors highlight the following factors: 1) students’ requests are decisive in the organization of blended learning; 2) specificity of the discipline; 3) pedagogical theories and approaches; 4) the relationship between teaching and students’ independent work. The effectiveness of the implementation of blended learning depends on the harmonious combination of digital technologies and the skill of their use. Blended learning is a qualitatively new approach that transforms the structure and content of teaching, changing the traditional roles of teachers and learners, as well as the learning environment. One of the components of blended learning is the "flipped classroom technology'' - a modern trend and an innovative way of organizing the educational process. The main advantage of the "flipped classroom" is that students acquire a number of competencies of the 21st century, such as the ability to solve problems independently, creativity, cooperation skills, and ICT literacy. Different models of the "flipped classroom" makes it possible to use a wider arsenal of forms of monitoring students' knowledge depending on the given tasks. A study on the technology of blended learning proved that this method contributes to the formation of students' learning abilities, and increases future teachers’ satisfaction and motivation. The analysis of research data proved that the technology is highly appreciated by teachers, provided there is an appropriate level of technical and pedagogical training and proper methodical materials. Keywords: higher education institution, future primary school teacher, professional training, information and communication technologies, digital educational environment, online learning, blended learning, blended learning models, "flipped classroom" technology.